STRATEGI INDONESIA – RRT DALAM MEMBERANTAS ILLEGAL LOGGING TAHUN 2009 – 2014 - Gigih Dhana Febrianto; Tri Cahyo Utomo (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Illegal logging is an environmental issue and to handle it, cooperation is needed, this research aims to describe the implementation of cooperation between Indonesia and Tiongkok in dealing with illegal logging in 2009-2014. On 15 September 2010, Memorandum of Understanding was formed Between the Ministry of Forestry of the Republic of Indonesia and the State Forestry Administration of the People's Republic of China concerning Cooperation in the Forestry Sector. The research, using qualitative method. This research using Liberalism theory. Illegal logging is the ineffectiveness of the implementation of the MoU that has been agreed to by both countries, this case happened because demand of wood in Tiongkok. The high demand from China has an impact on illegal logging cases in Indonesia. So wood supply from Indonesia is very much needed. Therefore, illegal timber smuggled from Indonesia is still high in Tiongkok, although the numbers are volatile